1998
DOI: 10.1002/(sici)1521-3951(199809)209:1<195::aid-pssb195>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The Defect Structure of New Glow Peak Generated from Heavily Annealed LiF : Mg, Ti

Abstract: Deconvolution analysis of optical absorption (OA) bands and thermoluminescence (TL) glow curves produced by annealing at and above 125 C for long times before irradiation permits the identification of a new peak in the glow curve and a new OA band at about 282 nm in optical absorption band of LiF:Mg, Ti. Due to their similar thermal decaying properties, it was decided that the generated new TL peak and OA band belong to the same type of defect centers, namely Z 2 -type centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The OA spectrum of β-irradiated TLD-100 at room temperature exhibits a series of OA bands ranging from 200 to 600 nm. There are at least four absorption bands with peak wavelengths at 250, 225, 310 and 380 nm [11,12]. The experimental investigations have shown that the band at 250 nm is related to F-centres [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OA spectrum of β-irradiated TLD-100 at room temperature exhibits a series of OA bands ranging from 200 to 600 nm. There are at least four absorption bands with peak wavelengths at 250, 225, 310 and 380 nm [11,12]. The experimental investigations have shown that the band at 250 nm is related to F-centres [2].…”
Section: Resultsmentioning
confidence: 99%
“…The experimental investigations have shown that the band at 250 nm is related to F-centres [2]. However, the origin of other bands is still uncertain but it is believed that they are related with Z 3 -centre, Mg 2+ -V − c -trimers and Mg 2+ -V − c -dipoles, respectively [11,12]. The energetic positions and FWHM of these bands are represented in table 1.…”
Section: Resultsmentioning
confidence: 99%